New cellulose crystallinity estimation method that differentiates between organized and crystalline phases. (15th June 2018) - Agarwal, Umesh P.; Ralph, Sally A.; Reiner, Richard S.; Baez, Carlos
Graphical abstract: Highlights: A new cellulose crystallinity estimation method is proposed. 93 cm −1 Raman band of crystalline cellulose was used to develop the method. The method is capable of differentiating between organized and crystalline cellulose. Crystallinity of hydrothermally treated poplar wood was estimated by the new method. Crystallinity of treated poplar depended on temperature of treatment. Abstract: A new method is proposed for estimation of cellulose crystallinity (CrI) based on 93 cm −1 Raman band in spectra of cellulose I materials. In this method (93-Raman), CrI was determined based on regression that was developed using the ratios of peak-heights of the 93 and 1096 cm −1 Raman bands (I93 /I1096 ). For calibration purposes, a set of eight samples, all derived from cotton microcrystalline cellulose Whatman CC31 were selected. When the peak intensity ratios (I93 /I1096 ) were plotted against the calculated CrIs of the calibration set samples, the plot showed an excellent linear correlation (R 2 = 0.9888). The 93-Raman method was used to estimate crystallinities of a number of cellulose materials including poplar wood samples that were hydrothermally treated at various temperatures. The wood 93-Raman CrI data showed that the method is able to differentiate between organized and crystalline phases of cellulose, a capability lacking in many other CrI estimation methods.